2010
DOI: 10.1016/j.diabres.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Circulating glycolaldehyde induces oxidative damage in the kidney of rats

Abstract: Renal failure is a key pathological issue in diabetic patients. Increased levels of advanced glycation end-products (AGEs) have been associated to diabetic complications, including diabetic nephropathy. Models of AGE-treated animals have been applied to evaluate the effect of such molecules on oxidative parameters involved in the pathogenesis and evolution of diabetes disease. However, little is known about the effect of glycating agents other than glucose. Here we investigate the effect of intravenously admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…8,29,30) In breast cancer cells, GA increased intracellular superoxide production and MnTMPyP, a superoxide dismutase/catalase mimetic, failed to protect cells from the GA-induced apoptotic cell death. 16,31) Studies have indicated that GA is oxidized by ROS, such as superoxide, during oxidative stress in isolated hepatocytes to form glyoxal and glyoxal subsequently induces cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8,29,30) In breast cancer cells, GA increased intracellular superoxide production and MnTMPyP, a superoxide dismutase/catalase mimetic, failed to protect cells from the GA-induced apoptotic cell death. 16,31) Studies have indicated that GA is oxidized by ROS, such as superoxide, during oxidative stress in isolated hepatocytes to form glyoxal and glyoxal subsequently induces cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…1,2) Although plasma GA level has not been quantified, its physiological concentration is estimated to range from 0.1 to 1 mm [8][9][10][11] and several in vitro studies have employed that range. [9][10][11] In this study, we demonstrated for the first time that GA at near-physiological concentration exerted biological effects on Schwann cells by effectively decreasing cell viability (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GLO plays an important role in the detoxification of aoxoaldehydes, mainly glyoxal and MG (Lorenzi et al, 2010). This enzyme catalyzes the formation of S-D-lactoylglutathione from MG and GSH, leading to reduced concentrations of its substrate.…”
Section: Discussionmentioning
confidence: 99%